BLACKBOARD APPLICATION TO PROMOTE STUDENTS’ WRITING SKILL AT SENIOR HIGH SCHOOL IN PALEMBANG - Santi Mayasari; Marleni Marleni; Masagus Firdaus (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
The purpose of this study was to improve the writing skills of XI grade high school students in Palembang. Researchers used a quasi method involving two groups of high school students in Palembang (experimental group and control group). The results of the study were (1) the experimental group pretest and the control group found that the experimental group got the lowest score of 21 and the highest was 63, while the control group got the lowest score of 23 and the highest score was 70, (2) the posttest of the experimental group and the Control Group, the results obtained were that the experimental group was able to obtain a mean value greater than the mean value of the control group. (3) Paired t-test; The results of the Pretest-Posttest Experimental Group showed that there was a very significant increase that occurred in the experimental group as a result of the implementation of LMS in the experimental group students' writing learning, the results of the Independent t-Test were obtained that the mean value of the experimental group was greater than the mean value of the control group, based on the results independent test analysis, it was found that the sig. (two-tailed) which is 0.000 with t-obtained 14,433. This can be interpreted that there is a positive influence on the application of LMS-based learning methods for the writing ability of high school students. Then, it can be seen that the F test value is 0.379 with sig. 0.539.